Evaluation of Obstetric Emergency Referral Cases at Dr. Cipto Mangunkusumo Hospital January - December 2008 - Dian Indah Purnama (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To have description and evaluation about obstetric emergency referral cases at obstetric emergency room of Dr. Cipto Mangunkusumo Hospital (RSCM) from January until December 2008. Method: This is a cross-sectional descriptive-analytic study with 458 secondary data samples from simple random sampling performed to all obstetric referral cases at obstetric emergency room of RSCM from January until December 2008. The data were pro-cessed for frequencies and bivariate analysis, and then further analyzed with multivariate analysis. Results: Patients’ age varied between 16 to 47 years old (27.78 ± 6.51). Grandemultiparous women had 51.9% morbidity/mortality (p = 0.024). Midwives were the majority of referee (73.1%), but 71.1% main obstetric emergency cases were referred by Ob/Gyn. There were 260 cases corresponded to main obstetric emergency with 88 cases diagnosed as hypertension. Most of the cases were referred due to threatened preterm labor (22.5%), with 74.7% reasons for referral were ’lack of facility’. Most of the cases had no complete referral record (91% cases had no referral time and 12.4% cases had no initial assessment). Our hospital’s mean response time was 8 minutes. From multivariate analysis, referee (OR for doctors and Obstetricians 2.751; 95% CI 1.475 - 5.129) and delivery method (OR for spontaneous delivery 0.412; 95% CI 0.227 - 0.750) were two most influent variables for obstetric emergency referral cases outcome. The MMR for this study was 253.2/100.000. Conclusion: Our referral system is still not efficient. It needs improvement and continuous input and facility fulfillment. [Indones J Obstet Gynecol 2010; 34-4: 164-9] Keywords: referral system, maternal mortality ratio, referral time, response time